Two cytotoxic triterpenes from cultures of a Kenyan Laetiporus sp. (Basidiomycota). (June 2017) - Chepkirui, Clara; Matasyoh, Josphat Clement; Decock, Cony; Stadler, Marc
Graphical abstract: Highlights: Two previously undescribed triterpenes Laetiporins A and B were isolated from Laetiporus sp. The strain Laetiporus sp. probably represents a new taxon. Five known triterpenes were also isolated. The isolated compounds exhibited significant cytotoxicity activity against various mammalian cell lines. Abstract: HPLC profiling of the mycelial culture of a poroid basidomycete collected in Mount Elgon, Kenya, which probably represents a new species of the genus Laetiporus, led to isolation of two previously undescribed lanostane type triterpenes.We propose the trivial names laetiporins A (1 ) and B (2 ). In addition, five known ones: dehydrosulphurenic acid (3 ), sulphurenic acid (4 ), eburicoic acid (5 ), 15α-hydroxytrametenolic acid (6 ) and trametenolic acid (7 ) were also isolated. The laetiporins (1–2 ) exhibited significant cytotoxic effects against various human cancer cells. The known compounds (3–5 ) and (7 ) also showed moderate cytotoxic activity, but none of the compounds showed any significant antimicrobial activity.